Synthetic report on the co-design and experimentation of agroecological technologies with dairy farmers of the Agroecological Living Landscape of Burkina Faso - Ouattara Songdah, Désiré; Sib, Ollo; Sanogo, Souleymane; Sodre, Etienne; Berre, David; Vall, Eric (2024)
In Burkina Faso, the implementation of an agroecological dairy farming system is a strategic necessity to meet the new expectations of the downstream of the dairy value chain, i.e. tasty and diversified dairy products made from local milk rather than milk powder. This is why, as part of the Agroecology Initiative (AEI), we have been working with dairy farmers on the co-design and testing of agroecological technologies. The approach consisted in setting up an agroecological package comprising: (i) forage and seed production plots, called Fodder Demo-Plot (FDP); (ii) farm co-product management advice using the CoProdScope tool; (iii) dairy poduction units using the Jabnde tool and (iv) a manure recovery system to produce manure in efficient covered manure pits. In 2023/24, some 60 dairy farmers affiliated to the Bobo-Dioulasso Dairy Innovation Platform volunteered to host the experiment. The FDPs produced a median value of 2,500 and 1,500 kg/ha of biomass for cereals and legumes respectively. The seeds produced enabled Fodders Demo-Plots to be re-established in year N+1 with over 100 farmers. The use of CoProdScope led to an increase in the contribution of crop co-products to the farm's fodder requirements, rising from 8.5 to 26% between year N and year N+1. The use of Jabnde made it possible to establish balanced diets for 48 lactating cows using forage from the Fodders Demo-Plots. Covered manure pits produced high-quality manure to improve soil fertility. Overall, the implementation of the agroecological package among dairy farmers has strengthened the resilience of the dairy production system in the Bobo-Dioulasso dairy basin. Farmers still need to improve: management of Fodder Demo-Plots; use and management of co-products; feeding dairy cows at an affordable cost and keeping abreast of weather alerts to know the best time to sow.